Knowledge, attitudes, and practice toward multisystem inflammatory syndrome in children among pediatrician in Eastern India: An online cross-sectional survey - Sanjay Kumar Sahu; Sibabratta Patnaik; Jyoti Ranjan Behera; Mukesh Kumar Jain; Mona Pathak (Wolters Kluwer Medknow Publications, 2021)
Background: Multisystem inflammatory syndrome in children (MIS-C) associated with severe acute respiratory syndrome-coronavirus-2 is a new life-threatening entity whose diagnosis and management warrant awareness and in-depth knowledge. This study intends to estimate the knowledge, attitudes, and practice toward MIS-C among pediatricians of eastern India. Subjects and Methods: A descriptive, web-based cross-sectional survey was conducted among pediatricians of eastern India between January 1 and March 31, 2021, where they were invited to participate irrespective of their experience in treating COVID-positive children. Results: The majority of pediatricians (≥95%) are aware of the terminology MIS-C, its clinical features, presence of raised inflammatory markers, its treatment, and follow-up. Although 75% were aware of the vulnerable age group, only 50% knew the exact timing of occurrence. Fever as a mandatory criterion for diagnosis was known to 62.6%. The majority (75%) agreed that positivity of any of the tests (reverse transcription polymerase chain reaction, antigen, or antibody) or history of contact with COVID is necessary for diagnosis. Kawasaki Disease and Toxic Shock Syndrome as a common differential diagnosis of MIS-C were agreed upon by 86%. Pediatricians working in COVID hospital were more confident in managing MIS-C than who are not working (72.8% vs. 38.6%). Steroid and intravenous immunoglobulin used as first-line treatment by 94% and 72%, respectively. Conclusion: Although the majority of pediatricians are now aware of MIS-C, still there is need for continuing medical education (CME) and interactive sessions with experts, to make them suspect, detect early and manage it more effectively.